การใช้จำนวนเซลล์โซมาติกในการประเมินปัจจัยด้านการรีดนมและการจัดการฟาร์ม ในฟาร์มโคนมของสหกรณ์โคนมท่าม่วง: The Use of Somatic Cell Counts to Evaluate Milking Practices and Farm Management in Dairy Farms of Tha-Muang Dairy Cooperative Limited - Pajonpiree, Ruethairat; Sindhuvanich, Sirinporn; Nakthong, Sasitorn; Rukkwamsuk, Theera (Asian Health, Science and Technology Reports, 2010)
Risk factor in milking practices and farm management associated with high somatic cell count in bulk milk study was conducted in 40 dairy farms of Tha-Muang Dairy Cooperative Limited. Previous records of bulk milk somatic cell count (BMSCC) geometric means, which ≥ 250,000 cells/ml indicates udder problems in farm, was used to classify farms into two groups (20 herds in each group). Questionnaire interview along with milk hygiene observation during afternoon milking was conducted. There were significantly different between two groups in their total number of cattle and milk production per cow. (p<0.05). Odd ratio analysis indicated that factor including cow showering before milking, CMT use, slipping cup during milking, inappropriate vacuum level of milking machine and liner running out of the condition were significant associated with being BMSCC ≥ 250,000 cells/ml. Poor milking hygiene causes mastitis and then being high BMSCC.